Potential use ofLentinus squarrosulusmushroom as fermenting agent and source of natural antioxidant additive in livestock feed - Abdullah, Noorlidah; Lau, C.C.; Ismail, S.M. (Wiley, 2015)
BACKGROUND: Fermenting feed has gained a lot of popularity in recent years owing to its renowned benefits to the livestock and feed quality. In the current study, Lentinus squarrosulus mushroom mycelium was tested for its potential as a fermenting agent and source of natural antioxidant in the feed. RESULTS: Phenolic content of methanolic and hot water extracts of the mycelium culture and its fermented maize ranged from 94.01 to 386.59mg gallic acid equivalents g-1 extract while the DPPH radical scavenging, CUPRAC, reducing power (RPA) and β-carotene bleaching (BCB) antioxidant activity had EC50 values ranged from 15.30 to 120.3, 0.74 to 4.71, 1.86 to 13.5 and 0.01 to 0.21mg mL-1, respectively. At 1.0-20.0mg mL-1, the extracts retarded 21.02-55.35% of lipid deterioration. Pearson correlation analysis revealed the phenolic content of the extracts has moderate correlation with DPPH (r = 0.589) and RPA (r = 0.580), also a high correlation with BCB antioxidant activity (r = 0.872). In principal component analysis, DPPH, CUPRAC and RPA were seen to be clustered tightly together while BCB antioxidant activity was grouped with the phenolic content. CONCLUSION: Overall, L. squarrosulus mycelium functioned as antioxidants via several mechanisms, involving either electron transfer or hydrogen transfer-based reactions suggesting it as a promising fermentation agent to enhance feed nutrition and the fermented maize as a valuable feed resource.